KAJIAN YURIDIS EMPIRIS TENTANG PARTAI POLITIK BERDASARKAN UNDANG-UNDANG NOMOR 2 TAHUN 2011 TENTANG PARTAI POLITIK (Studi Kasus Pada Partai Demokrasi Indonesia Perjuangan DPC Surakarta) - PRIBADI, BEKTI (Dinamika Hukum, 2020)
The purpose of this research is to examine and analyze the role of DPC PDI struggle of Surakarta city in conducting political education to the community in Surakarta. Reviewing and analyzing the factors that inhibit the DPC PDI struggle of Surakarta city in conducting political education to the community in Surakarta. The method of approach in writing is sociological juridical. The specification of this research uses analytical descriptive. Data sources use primary data and skunder data. Data collection techniques using interview and observation studies. To analyze the data, researchers use qualitative descriptive analysis methods. In the implementation of political education activities conducted by DPC PDI struggle of Surakarta city involve various circles, such as cadres, young generation and novice voters as well as for regional and prospective leaders and legislative candidates. Socialization and party school activities held. The conclusion that political education has been delivered and implemented in accordance with the legislation, the Pancasila ideology and the vision and mission of the party that wants to be conveyed to the people also cadernya. Factors that inhibit DPC PDI Surakarta City Struggle in implementing political education to the community in Surakarta is a low interest in the community in following political education and limited budget of funds. Therefore, the Government of Surakarta participated in assisting in the problem of funds especially for political education for the community through grant aid to political parties. Keywords: Political parties, Political education.